Prognostic and clinicopathological role of geriatric nutritional risk index in patients with diffuse large B-cell lymphoma: A meta-analysis - Cao, Dan; Zhang, Zongxin (Frontiers in Oncology, 2023)
Background Previous studies have explored the relationship between the geriatric nutritional risk index (GNRI) and survival outcomes of diffuse large B-cell lymphoma (DLBCL) cases, but the results were inconsistent. Consequently, the present meta-analysis was conducted to investigate how GNRI affects DLBCL and its function in terms of prognosis. Methods The Web of Science, PubMed, Embase, and Cochrane Library databases were thoroughly searched until January 18, 2023. We calculated combined hazard ratios (HRs) and 95% confidence intervals (CIs) to estimate the relationship between the GNRI and survival outcomes of patients with DLBCL. Results This meta-analysis included seven articles involving 2,353 cases. A lower level of GNRI predicted dismal overall survival (HR=1.40, 95% CI=1.25–1.56, p<0.001) and inferior progression-free survival (HR=1.46, 95% CI=1.19-1.80, p<0.001) of DLBCL patients. Moreover, a low GNRI was significantly related to Eastern Cooperative Oncology Group Performance Status ≥2 (odds ratio [OR]=4.55, 95% CI=2.75–7.54, p<0.001), Ann Arbor stage III–IV (OR=2.91, 95% CI=2.38–3.57, p<0.001), B symptoms (OR=3.51, 95% CI=2.34–5.29, p<0.001), and extranodal disease (OR=2.90, 95% CI=2.32–3.63, p<0.001). Conclusion A lower GNRI level predicted poorer short- and long-term prognosis in patients with DLBCL. A low GNRI was correlated with clinical factors of disease progression in DLBCL patients.